Study of the Evolution of SL-9 Impact Sites on Jupiter with the Kyunghee University 30 Inch Telescope - D. H. Son; Y. M. Song; S. G. Lee; H. Jin; K.-S. Kim; S. J. Kim (Journal of Astronomy and Space Sciences, 1995)
We observed SL-9 impact sites on Jupiter with a CCD and a R filter on the KyungHee University 30-inch telescope between July 17 and September 3, 1994. We identified impact sites of A, C, E, G, H, K, L, Q1, W and G-group. We calculated the moving velocity relative to System II and rotation period of the G, L sites to be from -8.0 to 8.8m/s, and 9h55m39.4s ± 34s, respectively. The diameters of G and L sites in our first observation were 1.95 x 10^4km, and 2.20 x 10^4km, respectively. In particular, we investigated the evolution of the impact sites by calculating the diffusing rates of the impact clouds.